An evaluation of the loading condition on mixed-mode stress intensity factors for CTST specimens made of 2024-T351 aluminum alloy. (December 2021) - Khatammanesh, Afshin; Farhangdoost, Khalil; Ghahremani Moghadam, Danial; Masoudi Nejad, Reza
Highlights: The unstable fracture of aluminum alloy is studied under mixed-mode loading conditions. A recently proposed loading device is employed for performing fracture experiments. 3D FE model using the M-integral approach are conducted to derive the SIFs. The fracture surface of specimen is analyzed using scanning electron microscope. A good consistency is observed between the obtained results. Abstract: In this paper, the fracture behavior of 2024-T351 aluminum alloy as a key engineering material in the aeronautical industry is investigated under various planar and nonplanar mixed-mode loading conditions involving pure mode-I and pure mode-III loadings. A newly suggested loading setup accompanied by compact tension shearing and tearing (CTST) specimens is utilized to perform fracture tests. Three-dimensional finite element modeling using the interaction integral method is carried out to derive the stress intensity factors (SIFs) and their ratios through the crack front for several mixed-mode configurations. The numerical results reveal that the coupled effect of modes II and III under mixed-mode I/II, I/III and I/II/III loading conditions is remarkable. Moreover, the amounts of SIFs at the center of the specimens are employed to predict the critical fracture loads according to different mixed-mode criteria. Also, scanning electron microscope (SEM) images of the fracture surfaces of CTST specimens are examined to evaluate the effect of different loading angles from a morphological viewpoint. A good consistency can be found among the results of the theoretical solutions of the criteria and the experimental observations for different loading conditions.